Viability Test and Breeding Growth on Poly-embryos Seeds. Issue 1 (June 2020) - Jasmi,; Ariska, N
Abstract: Seeds are mature ovules. One or more ovaries form in an ovary in a legume, but never more than one seed is formed in an ovary in a monocot. Each ripe seed always consists of at least two parts, namely: (1) Embryo, (2) Seed coat (Seed coat or testa). Embryo formed or derived from fertilized eggs (zygote) by undergoing cell division in the embryo. The seed coat is formed from the integument (one or more) of the ovules. In legumes generally, there are two layers of the seed coat. Every very young and growing seed always consists of three parts, namely: (1) Embryo, (2) seed coat, (3) Endosperm. Endosperm is a storage food storage network that is absorbed by the embryo before or during seed germination and is always present in very young seeds. Poly-embryos is the presence of more than one embryo in one seed, but these embryos do not always mature or mature, remain undeveloped or degenerate. The purpose of this research is to study the germination of one seed that has more than one embryo and to determine the growth of seedlings from poly-embryonic seeds. The results showed that the highest plant growth (plant height, number of leaves, fresh weight and dry weight of orange seeds) was found in orange seeds that had 1 embryo compared to orange seeds which had 2 and 3 embryos. Seed germination and growth are strongly influenced by the number of food reserves stored in seeds.